2023
DOI: 10.1002/deo2.206
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐institutional questionnaire on treatment strategies for superficial entire circumferential esophageal squamous cell carcinoma

Abstract: Objectives Recent innovations in prophylactic treatment with steroids have overcome the issue of esophageal stricture after endoscopic submucosal dissection (ESD), except in entire circumferential esophageal squamous cell carcinoma (EC‐ESCC). Current Japanese guidelines weakly recommend performing ESD for clinical epithelial/lamina propria EC‐ESCC with a longitudinal extension <50 mm upon implementing prophylactic treatment against stricture. However, the accurate indications for ESD in EC‐ESCC re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(64 reference statements)
1
0
0
1
Order By: Relevance
“…Many studies have identified longitudinal resection length as an independent risk factor for postoperative stricture and multivariate analysis in our study showed similar results [19,20]. we found that length was positively correlated with circumferential (r = 0.2297, P < 0.0001).…”
Section: Discussionsupporting
confidence: 87%
“…Many studies have identified longitudinal resection length as an independent risk factor for postoperative stricture and multivariate analysis in our study showed similar results [19,20]. we found that length was positively correlated with circumferential (r = 0.2297, P < 0.0001).…”
Section: Discussionsupporting
confidence: 87%
“…Die aktuelle japanische Leitlinie empfiehlt für zirkumferenzielle Läsionen JES Typ B1 mit einer maximalen Längenausdehnung von > 5 cm eine chirurgische Resektion oder Radiochemotherapie [16]. In einer aktuellen Publikation gab mehr als die Hälfte der befragten Zentren an, regelmäßig zirkumferenzielle Resektionen jenseits dieser Leitlinienkriterien durchzuführen [21]. Die ESD im Ösophagus wird auch in westlichen Zentren mit hohen En-bloc-und R0-Resektionsraten komplikationsarm durchgeführt [22,23].…”
Section: öSophagus Neoplasien Des Plattenepithelsunclassified